DEVELOPMENT OF SIMILARITY CRITERIA FOR PHYSICAL MODELING OF THE PROCESS OF ROADBED COMPACTION - Khankelov, Tavbay; Komilov, Samandar; Hudaykulov, Rashidbek; Salimova , Barno; Abdullaev, Khurshid (Journal of Applied Engineering Science, 2026)
This paper focuses on developing criteria for the physical modeling of roadbed compaction using a vibration roller. A rheological model of the process was    employed to establish the relationship between stresses and strains in soils with elastic-viscoplastic properties. Additional similarity criteria were utilized to characterize the design and technological specifications, as well as the initial and boundary conditions of the process. Based on these similarity criteria, a physical model of the working element of a vibration roller was created. A series of experiments was conducted to identify the key parameters of this working element. By analyzing the inverse relationships that define these key design and technological parameters, it is possible to determine optimal values for the essential parameters of the vibration roller.
Keywords: roadbed, similarity criterion, physical modeling, physical model, vibration roller